Radical writing center praxis : a paradigm for ethical political engagement - Greenfield, Laura (Utah State University Press, 2019)
"Imagining a writing center where directors and staff become agents in active social justice on campus and beyond. Introducing activist concepts and vocabulary challenging writing centers to recognize their complicity with oppressive systems. A call for a process of critical self-reflection and change to an activist paradigm"--Provided by publisher
Keywords: Writing centers -- Political aspects -- United States.; Writing centers -- Social aspects -- United States.; English language -- Rhetoric -- Study and teaching (Higher) -- Political aspects -- United States.; English language -- Rhetoric -- Study and teaching (Higher) -- Social aspects -- United States.; Academic writing -- Study and teaching (Higher) -- Political aspects -- United States.; Academic writing -- Study and teaching (Higher) -- Social aspects -- United States.; Education -- Political aspects -- United States.; Social justice and education -- United States.; Centres de communication écrite -- Aspect politique -- États-Unis.; Centres de communication écrite -- Aspect social -- États-Unis.; Éducation -- Aspect politique -- États-Unis.; Justice sociale et éducation -- États-Unis.; LANGUAGE ARTS & DISCIPLINES -- Composition & Creative Writing.; LANGUAGE ARTS & DISCIPLINES -- Rhetoric.; REFERENCE -- Writing Skills.; Education -- Political aspects; Social justice and education; United States; Electronic books.